A Mitogenome-Based Phylogeny of Pilargidae (Phyllodocida, Polychaeta, Annelida) and Evaluation of the Position of Antonbruunia - Sonja Huč; Avery S. Hiley; Marina F. McCowin; Greg W. Rouse (Diversity, 2024)
Pilargidae is a family of free-living and burrowing marine annelids. A lack of available molecular data for most of these species has precluded a molecular assessment of their phylogenetic relationships and has left uncertain the placement of Antonbruunia, which is hypothesized to be either a member of Pilargidae or its sister clade, the monotypic family Antonbruunidae. In this study, we describe the new species Antonbruunia milenae sp. nov., found at 845 m of depth off the coast of San Diego, California, USA, and we address the phylogeny of these organisms using 15 novel mitogenomes and multiple Sanger-sequenced loci. Our results show that Antonbruunia falls within Pilargidae, making Antonbruunidae a junior synonym of Pilargidae. Glyphohesione was transferred from Pilarginae to Synelminae, the previously unassigned genera Otopsis and Antonbruunia were shown to belong within Synelminae, and Hermundura was assigned to Phyllodocida incertae sedis. Sigambra was found to be non-monophyletic. Four different mitogenome gene orders were found among Pilargidae. Changes between the gene orders and the ancestral state gene order of the family were inferred. Two species have introns within the COI gene. These efforts represent a significant expansion of the available molecular resources for pilargids, as well as the basis for a more stable taxonomy.